A pilot study of topotecan in the treatment of serous carcinoma of the uterus. Issue 2 (1st February 2003) - Chambers, J. T.; Rutherford, T. J.; Schwartz, P. E.; Carcangiu, M. L.; Chambers, S. K.; Baker, L.
Abstract : A pilot study investigated topotecan (Hycamtin, GlaxoSmithKline, Philadelphia, PA), a topoisomerase I inhibitor, in treating uterine serous carcinoma, a typically unresponsive aggressive tumor. Fifteen patients were surgically staged, then treated with topotecan (1.5 mg/m 2, Days 1–5 every 21 days) as first-line therapy ( n = 12) or secondary to platinum failure ( n = 3). Patients received topotecan through six courses, disease progression, or unacceptable toxicity. Grade 3/4 hematologic toxicity prompted dose adjustments. Thirteen patients exhibited no gross evidence of residual disease postoperatively. At topotecan initiation, one patient had 5-cm and one had < 1-cm residual disease. Seventy-eight courses (median, six) were administered; 12 (80%) patients completed the specified protocol. Common serious toxicities included grade 3 neutropenia (33%), anemia (13%), and thrombocytopenia (13%). Eight patients received erythropoietin and/or granulocyte colony-stimulating factor. Median follow-up for 14 evaluable patients was 26 months (range, 13–40). Of 11 evaluable first-line topotecan patients, nine were alive at follow-up; five were disease-free. Of three second-line topotecan patients, two died and one was alive with disease 31 months post-treatment. One patient with measurable disease achieved a complete and one a partial response as assessed by computed tomography scan. Median progression-free survival was 25 months; median survival has not been reached at 26 months. Although topotecan's antitumor activity cannot yet be quantified, disease-free interval and survival outcomes compare favorably with other therapies in uterine serous carcinoma. Further evaluation of topotecan in this population is warranted.